An Evaluation of Library Automaton in Some Ghanaian University Libraries - Amekuede, J.K. (University of Ghana, 2002)
Automation in libraries has had far-reaching effects on everyday practices and librarianship as a profession. The use of computers in libraries has had and it is continuing to have a profound effect on all aspects of library and information work. As more information is made available in a variety of formats and in a variety places, the need to manage information effectively becomes critical. And for university libraries to maintain their positions as the University's information centre, they will have to play leading roles in the technological revolution. This thesis is an evaluation of library automation in Ghana's university libraries. The study was undertaken to find out which library processes have been automated in Ghana's three older university libraries namely, the Balme Library, the Kwame Nkrumah University of Science and Technology(KNUST) Library and the University of Cape Coast (UCC) Library. Relevant literature in the area of automation was revised. Using data obtained through the use of questionnaires and interviews, the study examined areas of general automation, automation of specific library processes, networking, internet connectivity, training, the future of library automation at the University libraries and major constraints to library automation. The sampling technique used in study is the purposive sampling method. This sampling technique allowed the researcher to use his skill and prior knowledge to choose respondents. Using this technique, the following samples were selected; 59 for Balme Library, 35 for KNUST Library and 44 for UCC library. The libraries of the three older universities in Ghana, that is, the Balme Library, University of Ghana, Kwame Nkrumah University of Science and Technology library, the University of Cape Coast library were chosen as the focus of the study because they have embarked on automation of their library processes. The study found out that even though the university libraries realize the importance of library automation, they are hampered by lack of funds, lack of support from the university administrations and lack of skilled staff to embark on the automation of all library processes. It was also revealed that none of the libraries have an OPAC (Online Public Access Catalogue). The study concludes with recommendations that would enhance the university libraries drive towards automation of their library processes and ensure effective and efficient use of the new technology to raise the image of the libraries and give their library clients more services. The following recommendations are made based on the findings of this research. The recommendations are made to serve as a guide to all libraries in general and especially university libraries in Ghana which intend to automate their library processes. The recommendations are for University Administrators, University Librarians, Librarians and policy makers. 1. Since there can be no library automation without computers and their accessories, the required number of computers and accessories should be purchased for the university libraries. In fact, the libraries should be allowed to purchase computers of their choice. 2. In addition, the libraries should also make sure that they purchase the latest computers on the market if they are allowed to do the purchases themselves because the information technology market is in a state of flux. Computers in the library should be used for automation of library processes. 3. Sufficient funds should be made available by the university administrations to fund automation projects. 4. Library software is very important in library automation. It is recommended that Library software for all library processes should be acquired. Librarians should be taught skills, which will enable them identify appropriate software for their library needs. They can also be taught how to write in-house software for their libraries especially in sections where their collections are not so large. 5. The evaluation revealed that even though all the university libraries have strategic plans, these plans have not been updated to take care of current trends. It is recommended that these strategic plans should be updated regularly and be implemented within time frames. 6.Some of the university libraries evaluated do not have an Electronic Support Unit. It is recommended that as a matter of urgency all these libraries should engage the services of a system analyst and set up Electronic Support Units. Without this support, problems associated with computer hardware and software and access problems cannot be easily or quickly solved. Such a unit can also increase the scope of IT products and other activities in the libraries. 7. Local Area Networks (LAN) should be set up in all the university libraries. LANs can also be very useful when these libraries have Online Public Access Catalogues (OPACs) because library users can then search the library's catalogue anywhere in the library. 8.Library staff should be made aware of ongoing projects in the library, especially those to do with automation, so as to create the awareness and feeling of belonging. The staff, on the other hand, should be curious about things going on in the library concerning automation. 9. More often than not when people talk of automation, they are referring to hardware and software, ignoring the human aspects of automation, specifically staff and user training. The study revealed that none of the libraries surveyed has a firm training programme in place. It is therefore, recommended that a training programme should be in place in all the university libraries. The training should be ongoing because when we automate, we are not only learning how to use the automated system; we are in fact learning new jobs. No operation is better than its personnel. The advancement of individuals who operate library automation programmes is a critical element in the success of automation.
MPhil. Library Studies
Keywords: Automation; Libraries; Computers; University's Information Centre; Kwame Nkrumah University of Science and Technology(KNUST) Library; University of Cape Coast (UCC) Library; Balme Library; OPAC (Online Public Access Catalogue); Ghana; Electronic Support Unit; Local Area Networks (LAN)